The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s11001-021-09432-2
|View full text |Cite
|
Sign up to set email alerts
|

3D crustal-scale structure of the West Iberia margin: a novel approach to integrated structural characterization of passive margins

Abstract: Hyperextended margins are very heterogeneous along the entire length of the margin, so the definition of tectonic domains made exclusively from 2D seismic sections presents serious limitations. In this work we present an approach of the 3D crustal-scale structure of the West Iberia margin (WIM) by modelling eight lithospheric sections, using seismic, wells and gravity data. The continuous nature of gravity data allowed us to propose a new map of tectonic domains within the WIM. Maps of total horizontal (THD) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 111 publications
1
3
0
Order By: Relevance
“…Namely, the boundary between the OMZ and SPZ, which can be inferred to run north of Vila Franca de Xira, links in the offshore with a major NW–SE lineament observed on gravity (Figure 3) and would define the southern limit of the Galicia Bank. This is consistent with the observations of Granado et al (2021) who already suggested that the limit between the northern and central sectors of the WIM follows a NW–SE orientation. This offshore extension of the SPZ–OMZ boundary links with the outermost reach of Profile B, at the boundary between the hyperextended and strongly rifted domains.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Namely, the boundary between the OMZ and SPZ, which can be inferred to run north of Vila Franca de Xira, links in the offshore with a major NW–SE lineament observed on gravity (Figure 3) and would define the southern limit of the Galicia Bank. This is consistent with the observations of Granado et al (2021) who already suggested that the limit between the northern and central sectors of the WIM follows a NW–SE orientation. This offshore extension of the SPZ–OMZ boundary links with the outermost reach of Profile B, at the boundary between the hyperextended and strongly rifted domains.…”
Section: Discussionsupporting
confidence: 93%
“…The total horizontal derivative of the upward continuation of the Bouguer anomaly has been calculated as strong gravitational gradients are interpreted to mark the proximal and distal domains (Fernandez et al, 2020; Granado et al, 2021) (Figure 3). Details on the seismic and gravity data used as well as interpretation workflow followed in this study can be found in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the NE Atlantic, a similar marine MT acquisition campaign in the Porcupine Basin or Rockall Trough could settle long-standing debate on the existence of serpentinization (Reston, 2009). Finally, a calibration MT survey along exhumed mantle zone of the Western Iberian Margin (Granado et al, 2021) could broaden the scope of our research to magma-poor passive margins.…”
Section: Discussionmentioning
confidence: 86%
“…Using seismic, wells and gravity data, Granado et al (2021) modelled a more complex 3D crustal scale structure of the WIM.…”
Section: Crustal Structure and Domains Of The Wimmentioning
confidence: 99%